Mladinska književnost med krščanstvom in socializmom - Svetina, Peter (Jezik in slovstvo, 2009)
The Brotherhood of the Blue Seagull by Tone Seliškar is one of the central works of contemporary youth narrative prose. The work was first published in book form in 1936, when the Slovene middle class had a central social role, while the revised edition was published in 1948, in the time of the newly emerged socialist regime. The new social circumstances also had an influence on the different conceptual point of departure in the novel. A comparison of and commentary on the changes of the pre-war and post-war editions of the story is the topic of the present article.
Keywords: 1. pol. 20.st.; meščanstvo; povest; powest; Seliškar; Seliškar, Tone; Seliškar, Tone: Bratovščina Sinjega galeba; Slovene literature; slovenska književnost; slovenska mladinska književnost; socialism; socializem